Reconstruction of the Criminal Liability of State-Owned Enterprise Directors in Managing the Tin Business Based on the Business Judgment Rule and Anti-Corruption Principles - Muhammad Zulkarnaen Dharmawi; Subianta Mandala (Journal Customary Law, 2026)
This study examines the construction of criminal liability of state-owned enterprise (BUMN) directors in managing the tin business, which faces tensions between the corporate law approach and the criminal law on corruption. The background of this study is the phenomenon of the criminalization of business policies arising from the dominance of state loss parameters without considering the characteristics of business risks. The main problem lies in the absence of a clear boundary between business risks and corruption crimes and the lack of integration of the Business Judgment Rule within the criminal law system. This study aims to analyze the weaknesses of the applicable legal construction and formulate a reconstruction model for criminal liability that is fairer and more proportional. The method used is normative juridical with a statutory, conceptual, and comparative approach, as well as a prescriptive qualitative analysis of primary and secondary legal materials. The results show that the current legal construction tends towards a consequence-based and position-based approach that potentially ignores the element of fault. The Business Judgment Rule has not been explicitly recognized in criminal law and therefore does not function as a protection mechanism for directors acting in good faith. The proposed reconstruction emphasizes the integration of the Business Judgment Rule as the basis for limiting criminal liability, affirming the element of mens rea, and formulating objective parameters in distinguishing business risks from corrupt acts. This approach is expected to create a balance between protection for directors and the effectiveness of eradicating corruption.